Organosolv fractionating pre‐treatment of lignocellulosic biomass for efficient enzymatic saccharification: chemistry, kinetics, and substrate structures. (11th April 2017) - Zhao, Xuebing; Li, Siming; Wu, Ruchun; Liu, Dehua
Abstract: Pre‐treatment to increase cellulose enzymatic hydrolyzability is a prerequisite step for bioconversion of lignocellulosic biomass. The final objective of pre‐treatment is to increase cellulose accessibility to cellulase enzymes, which can be done by either removing hemicelluloses or delignification or modifying lignin structure. Organosolv fractionating pre‐treatment (OFP) achieves a fractionation of biomass in a one‐pot process with greatly increased cellulose digestibility. In this review, the research progress in recent years on the acid and alkali‐catalyzed OFP processes has been discussed, in terms of the process modes, chemistry, pre‐treatment kinetics as well as substrate structures. It is concluded that OFP not only improves cellulose digestibility but also shows great promise as an entry to biomass biorefining for co‐producing various chemicals and fuels; however, the economic feasibility of the OFP process has to be improved by reducing the energy consumption for solvent recovery and developing more products with higher added values. Finally, the challenge and perspective of OFP are further discussed. © 2017 Society of Chemical Industry and John Wiley & Sons, Ltd